Delirium in the Critically Ill Child. Issue 5 (September 2017) - Norman, Sharon; Taha, Asma A.; Turner, Helen N.
Abstract : Purpose/Objective: The purposes of this article are to describe the scientific literature on assessment, prevention, and management of delirium in critically ill children and to articulate the implications for clinical nurse specialists, in translating the evidence into practice. Description: A literature search was conducted in 4 databases—OvidMEDLINE, Cumulative Index to Nursing and Allied Health Literature, PsychINFO, and Web of Science—using the terms "delirium, " "child, " and "critically ill" for the period of 2006 to 2016. Outcome: The scientific literature included articles on diagnosis, prevalence, risk factors, adverse outcomes, screening tools, prevention, and management. The prevalence of delirium in critically ill children is up to 30%. Risk factors include age, developmental delay, severity of illness, and mechanical ventilation. Adverse outcomes include increased mortality, hospital length of stay, and cost for the critically ill child with delirium. Valid and reliable delirium screening tools are available for critically ill children. Prevention and management strategies include interventions to address environmental triggers, sleep disruption, integrated family care, and mobilization. Conclusion: Delirium is a common occurrence for the critically ill child. The clinical nurse specialist is accountable for leading the implementation of practice changes that are based on evidence to improve patient outcomes. Screening and early intervention for delirium are key to mitigating adverse outcomes for critically ill children.